Manifestations of Urban Interiority in Delhi Gate Bazaar of Lahore - Shah, Sarah Javed; Muro, Carles (UI Scholars Hub, 2023)
In the contemporary debate, the notion of interiority has expanded beyond the confines of the interior, in the urban realm, as a conjunction of urban and interior conditions. This article aims to contribute to the discourse, using the lens of urban interiority to explore the unique spatial character and distinct cultural practices in Lahore’s Delhi Gate Bazaar. The bazaar exists on a linear passageway, the Royal Trail, as a network of interior, exterior, and in-between spaces—establishing a spatial continuum by blurring the boundaries between the public and private and uninterrupted flow of spaces from outside to inside. This urban space has a strong sense of history, culture, and traditions; constructing personal and collective engagement through modes of space inhabitation and appropriation. These practices include temporal improvisation and modification of certain aspects for everyday use and environmental alteration for achieving thermal comfort, along with synchronised occurrences of cultural traditions and commercial activities. This article interprets observations through drawings to describe the experience of space through gradations of interiority and transition through thresholds, constructing visual narratives of diverse uses, activities, and the interaction between people, objects, and space.